The Influence of TikTok Pandawara Group Media Exposure on Increased Environmental Awareness Among University of Pancasila Students - Ryvaldy Alfachredz (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
Social media facilitates interaction among people through various social activities such as communication and content sharing. TikTok is currently popular among the public. Pandawara Group, an environmentally conscious community, uses TikTok to spread environmental awareness through videos. This study aims to evaluate the influence of TikTok content from Pandawara Group on the environmental awareness of Universitas Pancasila students. The research method used is quantitative with a positivist paradigm and an explanatory research type. The sample involves 100 active students from Pancasila University for the 2023/2024 period, using linear regression for data analysis. The results show a significant influence between exposure to Pandawara Group's TikTok content and the increase in environmental awareness among students. This study highlights the importance of TikTok in shaping environmental awareness among students. Informative and inspiring content from Pandawara Group significantly contributes to the increase in environmental awareness. Environmental campaigns through social media like TikTok have proven effective in raising environmental awareness. These findings emphasize the need for active roles of organizations and individuals in using social media as a tool for education and inspiration regarding environmental issues.